Guidance and Counseling Teachers' Strategies in Handling Students with Duck Syndrome Through Cognitive Behavioral Therapy-Based Psychoeducation - Nailis Sa’adah; Bagus Amirulloh (Interpersonal: Jurnal Bimbingan Konseling Islam, 2026)
Students experience duck syndrome, caused by a negative self-perception, when facing academic demands as well as the demands of working to support their families’ finances, thereby experiencing a decline in self-confidence, a loss of motivation to learn, and social withdrawal. This study aims to describe the application of psychoeducation based on cognitive behavioral therapy by guidance counselors in handling 11th-grade students experiencing the duck syndrome and to identify the barriers and supporting factors for guidance counselors in conducting psychoeducation based on cognitive behavioral therapy for 11th-grade students experiencing the duck syndrome at Madrasah Aliyah Mabdaul Falah Larangan Pamekasan. This study is a qualitative study of a descriptive nature. Data collection was conducted using observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of cognitive behavioral therapy-based psychoeducation by guidance counselors in handling 11th-grade students experiencing duck syndrome at Madrasah Aliyah Mabdaul Falah Larangan Pamekasan was carried out effectively. It was delivered through four steps: first, building self-understanding; second, identifying and changing negative thoughts; third, stress management skills, through time-management exercises using sticky notes; and finally, an evaluation to assess changes in the students. A limiting factor in the implementation of this activity was noise from other classrooms, which occasionally disrupted student concentration. Supporting factors included collaboration between the guidance counselor, subject teachers, and homeroom teachers; a positive relationship between the guidance counselor and students; supportive school facilities and policies; and the use of effective media and methods.